TAFSSA District Agrifood Systems Assessment in Nepal 2023: Community - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at supporting actions that enhance equitable access to sustainable, healthy diets, improve farmers’ livelihoods and resilience, and conserve land, air, and water resources in South Asia. The TAFSSA district agrifood systems assessment seeks to provide a reliable, accessible, and integrated evidence base linking farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed as a district-level multi-year assessment. Data were collected in March-April 2023 in the Surkhet and Banke districts in Nepal. Three respondents were interviewed per household: a female adult (aged 20+ years) primarily responsible for managing the household, a male adult (aged 20+ years) primarily responsible for agricultural activities, and an adolescent (aged 10-19 years). The assessment also included a community questionnaire that interviewed a key informant in the district villages. The community questionnaire was conducted using pretested, structured questionnaires. Information was collected on village demographic composition, wage rates, machine rental costs during the agricultural season, infrastructure, and groundwater and land use.